2019
DOI: 10.1519/jpt.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Improved Functional Performance in Individuals With Dementia After a Moderate-Intensity Home-Based Exercise Program: A Randomized Controlled Trial

Abstract: The current intervention used a Strength-Based Approach to facilitate implementation of exercise activities that could be completed by the sample. Therefore, integration of these techniques into mainstream clinical practice and research should be feasible with this patient population. Future research directions and implications of these findings also are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
1
29
1
Order By: Relevance
“…The incidence of recorded adverse events during exercise sessions in the study was higher than previously reported incidences in people with dementia 27,45. This difference could be explained by a relatively high prevalence of medical conditions such as osteoarthritis, stroke, depression, and delirium in our cohort.…”
Section: Discussioncontrasting
confidence: 70%
“…The incidence of recorded adverse events during exercise sessions in the study was higher than previously reported incidences in people with dementia 27,45. This difference could be explained by a relatively high prevalence of medical conditions such as osteoarthritis, stroke, depression, and delirium in our cohort.…”
Section: Discussioncontrasting
confidence: 70%
“…These inconsistent findings may be related to different study designs, gait assessments, interventions, and sample characteristics between previous research and our study. For example, studies considering walking speed in single task condition and reporting positive effects are characterized by more walking tasks included in the intervention [ 17 , 19 21 , 23 , 40 , 41 , 43 ], higher exercise intensities [ 19 , 20 , 43 ], participants with less cognitive impairments [ 19 , 21 , 43 ], worse baseline walking performance [ 17 , 18 , 22 , 23 , 46 ], better baseline walking performance [ 19 , 20 , 43 ], as well as assessing gait performance during fast walking [ 27 , 29 , 31 , 48 ] compared to our study. While the first four observations reflect the results and indications of this study, better baseline walking performance may enable instructors to implement higher exercise intensities and larger amounts of specific walking tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Practice with appropriate level of challenge and intensity [5][6][7][8]44 All components of training:…”
Section: Author Manuscriptmentioning
confidence: 99%
“…A recent study demonstrated that a functional exercise program using this framework improved strength, balance, and gait speed outcomes in individuals with dementia. 5 We apply the Strength-Based model to guide therapists in recognizing, understanding, and exploiting the motor learning and relationship capabilities of IwCI in the context of VPT.…”
mentioning
confidence: 99%